The Mechanisms of Plasticity of Nociceptive Ion Channels in Painful Diabetic Neuropathy - Joksimovic, Sonja L.; Jevtovic-Todorovic, Vesna; Todorovic, Slobodan M. (Frontiers in Pain Research, 2022)
Treating pain in patients suffering from small fiber neuropathies still represents a therapeutic challenge for health care providers and drug developers worldwide. Unfortunately, none of the currently available treatments can completely reverse symptoms of either gain or loss of peripheral nerve sensation. Therefore, there is a clear need for novel mechanism-based therapies for peripheral diabetic neuropathy (PDN) that would improve treatment of this serious condition. In this review we summarize the current knowledge on the mechanisms and causes of peripheral sensory neurons damage in diabetes. In particular, we focused on the subsets of voltage-gated sodium channels, TRP family of ion channels and a CaV3.2 isoform of T-type voltage-gated calcium channels. However, even though their potential is confirmed well validated in multiple rodent models of painful PDN, clinical trials with specific pharmacological blockers of these channels have failed to exhibit therapeutic efficacy. We argue that understanding the development of diabetes and causal relationship between hyperglycemia, glycosylation and other post-translational modifications may lead to the development of novel therapeutics that would efficiently alleviate painful PDN by targeting disease-specific mechanisms rather than individual nociceptive ion channels.